“Quality Indicators in Diagnostic Assessments: a GPS for the intervention to promote the rights and protection of children and young people” - Ruxa, A. (Colloque Scientifique – “Les Indicateurs de Qualité de l’Accompagnement de l’Enfant en Protection de l’Enfance”, 2020)
The identification of a dangerous situation for a child is the starting point that legitimizes the activation of subsidiary mechanisms for their protection. In Portugal, when the first level of intervention (community, with its formal or informal institutions) is unable, consensually with families and children, and adequately and sufficiently, to put an end to the situation of danger (also depending on their severity), there is referral to the Commission for the Protection of Children and Youth in the area that is territorially competent (CNPCJR et al., 2011; LPCJP - annex of Law 147/99 of 1 September). It is in the specific intervention of these interdisciplinary and interinstitutional entities, “non-judicial” and “with functional autonomy” (legitimized by the families and children from the age of 12), on which we will focus our attention. After analyzing the eligibility of the situation (focusing on the report in view of the characteristics of the incident, the child, the parents/caregivers and the social-family environment), the informed consent (written) is obtained to start/continue the assessment. The way in which the families and children are informed so that can take decision on giving or not consent is the first step in the collaborative helping relationship on which all subsequent intervention will depend (Ruxa, 2013). The decision-making process corresponds to a critical process of child protection interventions (Child Welfare Information Gateway, 2003; State Government Victoria, 2006; Houston, 2015; Capacity Building Center for States, 2017). It is believed that the ability to collect quality information and the collegiate, democratic and argumentative deliberative act based on the ethics of discourse to achieve greater consensus and quality (Habermas, 1992; Palmero, 2015; Ruxa, 2017; Dahler-Larsen, 2019) will enable better informed decisions to be made. The quality indicators in assessments in the context of child protection – GPS for the most appropriate taking of protective and welfare-promoting measures, based on evidence, are being grouped and presented in the literature in a relatively consensual way. The indicators are divided between analyzes of risks, needs, parenting skills, family and ecological factors, the potential for family change, among others (Department of Health, Department for Education and Employment and the Home Office, 2000; CNPCJR et al., 2011; Calder et al., 2012; Ministry of Children and Youth Service - Ontario, 2016). However, we alert for two issues: the factors that can negatively influence the quality of the evaluations; and for the fact that the greater standardization aimed at improving their quality does not eliminate the space for professionals' discretion (Banks, 2004) in view of the final decision-making process.